ANALISIS KEMAMPUAN LITERASI DIGITAL MAHASISWA PGSD FKIP UNRI DALAM PEMBELAJARAN DARING - Nurul Hidayati; Zufriady2; Zariul Antosa (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article describes how far the digital literacy skills of PGSD FKIP UNRI students are in online learning. The type of research in this article is descriptive quantitative research. The research was conducted in the PGSD FKIP UNRI Study Program with a population of 361 students and a sample of 163 PGSD FKIP UNRI students. Research data was in the form of primary data. The method of data collection in the study used questionnaires via google forms which were distributed and shared via WhatsApp messages. The technique of data analysis used in this study was to calculate the percentage of data from each indicator, interpret the percentage score, and then analyze each indicator. Thus, the results obtained from this study were an average score of 78.98% with a very good category